STRATEGI KEBIJAKAN KEPALA SEKOLAH DALAM PENINGKATAN MUTU PENDIDIKAN - Ummidlatus Salamah Iin Nur Aini Siti Aisyah (EDUTHINK: Jurnal Pemikiran Pendidikan Islam, 2022)
The policy of improving the quality of education is directed at improving the quality of education that refers to the national education standard. This study aims to explain the principal's policy in improving the quality of education at SDN Dahor, Grabagan, Tuban. The research approach used is a qualitative research approach with qualitative descriptive research. The results showed that sekolah principals in improving the quality of education at SDN Dahor through: a) direct guidance from the principal of SDN Dahor, b) Involving teachers in thematic learning training held by the cluster, c) involving teachers in KKG, d) holding discussions between teachers in schools, e) involving teachers in workshops on information technology as a learning medium, f) principals holding lesson studies for SDN Dahor teachers, g) teachers taking part in curriculum training organized by the service, h) for teachers who have fulfilled professional development sustainable development (PKB) in the form of training from school principals on writing scientific papers in the form of classroom action research (CAR).